Screening the asymptomatic soldiers after a stay in sub-Saharan Africa. A retrospective observational study. Issue 39 (January 2021) - Vanbrabant, Peter; Damanet, Benjamin; Maussen, Chris; Van Esbroeck, Marjan; Soentjens, Patrick
Abstract: Background: Many tropical clinics offer post-travel screening for parasitic infections in asymptomatic travellers. However, literature on attack rates and incidence rates of parasitic infections is scarce. Method: All military personnel returning from a tropical region during the year 2018 were tested for the presence of antibodies against Strongyloides stercoralis, Schistosoma and Entamoeba histolytica . Test results were compared with previous results if available to distinguish recent and old infection. Results: In total, 949 soldiers were included in the study. The median age was years 31 (IQR: 26–41), 96.3% were male. The median duration of stay in the tropics was 35 days (IQR: 14–90). The destination was predominantly central Africa. Serological tests were positive for S. stercoralis in 10 patients (1.1%), Schistosoma in 3 (0.3%), and E. histolytica in 16 (1.7%). The attack rates were 0.84, 0.32 and 1.69 respectively. The incidence rates were 3.99, 1.49 and 7.97 respectively. Conclusions: The risk for parasitic infection in the asymptomatic returning soldiers is low. However, the potentially serious complications of unrecognised parasitic infection can legitimise systematic screening.